Peran Ekstrakurikuler Keagamaan Islam dalam Meningkatkan Kesadaran Beragama Siswa di Madrasah Ibtidaiyah Islamiyah Banjarpoh Pulorejo Ngoro Jombang - Fathur Rofi'i; Khoirul Huda; Abdul Jabar (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
ABSTRACT This study aims to determine the role of religious extracurricular activities in increasing students' religious awareness and to identify the types of religious extracurricular activities available at MI Islamiyah Banjarpoh Pulorejo Ngoro Jombang. This qualitative study uses a descriptive approach to identify the types of religious extracurricular activities available at MI Islamiyah Banjarpoh Pulorejo Ngoro Jombang. Data collection techniques used observation, documentation, and interviews. Data analysis used three stages: data reduction, data presentation, and conclusion drawing. The results indicate that Islamic religious extracurricular activities at MI Islamiyah Banjarpoh are significant in shaping and increasing students' religious awareness. The types of religious extracurricular activities are quite diverse, including Quranic recitation, Islamic studies, congregational prayer, commemoration of Islamic holidays (PHBI), hadrah art, and social and religious activities. The success of religious extracurricular activities is influenced by several factors, including support from the school and teachers, parental involvement, students' internal motivation, and a religious school environment. Keywords: Islamic Religious Extracurricular Activities, Religious Awareness, Students